2018
DOI: 10.1111/jgs.15209
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties with Fine Motor Skills and Cognitive Impairment in an Elderly Population: The Progetto Veneto Anziani

Abstract: Difficulties with fine motor skills are common in older adults, and assessing them may help to identify early signs of dementia, subjects at high risk to develop cognitive decline, and individuals who can be referred to specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Sensorimotor performances have been investigated by several methods available in clinical settings like gait, postural equilibrium ( 5 7 ) or neuropsychological tests ( 8 , 9 ). Markers of impaired manual dexterity have also been used ( 3 ), and a recent longitudinal 4-year cohort study found that prolonged time taken in two simple manual dexterity tasks (including putting on and buttoning a shirt) was related to higher risk of developing cognitive decline [according to MMSE; ( 10 )]. Sensorimotor markers are considered independent of educational level ( 11 ), which is an advantage for clinical use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensorimotor performances have been investigated by several methods available in clinical settings like gait, postural equilibrium ( 5 7 ) or neuropsychological tests ( 8 , 9 ). Markers of impaired manual dexterity have also been used ( 3 ), and a recent longitudinal 4-year cohort study found that prolonged time taken in two simple manual dexterity tasks (including putting on and buttoning a shirt) was related to higher risk of developing cognitive decline [according to MMSE; ( 10 )]. Sensorimotor markers are considered independent of educational level ( 11 ), which is an advantage for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…First, as a potential marker, what type of manual dexterity task and which type of performance variable is optimal? Performance measures previously used were most often global task-based measures, i.e., time taken to complete task ( 5 , 6 , 10 ). Thus, it remained unclear what aspect of sensorimotor control was being measured, making the rationale for detecting cognitive decline uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have demonstrated that coordination and stability are primarily associated with basal ganglia, the cortical connections and functions are critical [ 20 , 21 , 22 , 23 ]. In a population-based longitudinal study of 2361 older patients, the time required to wear a shirt or complete a manual dexterity task was significantly longer in the preclinical phase of dementia [ 18 ]. In the Parkinsonism pathophysiology, early changes start from the medulla and pontine tegmentum and then slowly progress to the substantia nigra dopaminergic system during the mid-stage and finally to cortical deposition of Lewy bodies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD patients with mild cognitive impairment (MCI) perform significantly worse in subtests of precision dexterity and velocity of arm-hand movements than PD patients without MCI [ 10 , 18 ]. In addition, in a study comparing the finger tapping patterns among patients with AD, PD, and MCI and healthy older adults, higher finger tapping variability was negatively associated with cognition; moreover, patients with PD demonstrated more taps with shorter intertap intervals [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation